PROFIL KOMPETENSI IMPLEMENTASI KURIKULUM MERDEKA PADA GURU BIMBINGAN DAN KONSELING - Romiaty, Romiaty; Suriatie, Mimi; Karuniaty Sangalang, Oktamia; Feronika, Nopi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The Independent Curriculum is an educational innovation that aims to give schools the freedom to adapt their curriculum to students' needs and preferences. The aim of this research is to obtain an overview of the competency profile of Guidance and Counseling Teachers in Palangka Raya in implementing the independent curriculum. This research method is quantitative research with a survey type. With data analysis techniques is percentages. The research sample was 50 Guidance and Counseling Teachers in Palangka Raya. The results of the research show that there are 37 or 74% of BK teachers who have in-depth knowledge of the independent curriculum; 39 BK teachers or 78% have the ability to map student potential; 33 guidance and counseling teachers or 66% have skills in designing individual guidance programs; 42 BK teachers or 84% have effective counseling and communication skills; 46 BK teachers or 92% have collaboration and partnership skills.